FROM LONDON TO TASHKENT: INTEGRATING VICTORIAN LITERATURE INTO UZBEK EFL CURRICULA. (INTERNATIONAL CONFERENCE ON ADVANCE SCIENCE AND TECHNOLOGY, 2025)
The primary aim of this research is to explore the potential of integrating Victorian literature into the English as a Foreign Language (EFL) curriculum in Uzbekistan. This study seeks to examine how canonical works of Victorian authors such as Charles Dickens, Charlotte Brontë, and Thomas Hardy can enhance students’ language competence, cultural awareness, and critical thinking skills. Additionally, the research aims to identify effective pedagogical strategies and curriculum design models that align with both national education standards and communicative language teaching principles.